PERILAKU DELIKUENSI DAN RESILIENSINYA DI SMA NEGERI 13 SEMARANG - Anggita Amelia Listiyani, Fulia Aji Gustaman (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
The purpose of the study was to determine the application of character education applied at SMA Negeri 13 Semarang to overcome deliberative behavior that occurs in students. The method used in this study is purposive qualitative. Researchers took data through interviews with 7 resource persons, besides that researchers also made observations in the school environment of SMA Negeri 13 Semarang. The data obtained is then analyzed in several stages, namey reduction, presentation, and coclusions. The result of this study have found that the application of character education carried out at SMA Negeri 13 Semarang can reduce the deliberative behavior carried out by students. The application of character education must also be supported and strengthened with the support of parents and the surrounding environment.